INCREASING TEACHER PERFORMANCE IN THE DEVELOPMENT OF TEACHING MATERIALS THROUGH ACADEMIC SUPERVISION AS AN EFFORT TO INCREASE QUALITY ACHIEVEMENTS IN SDN 23 BALAI NARAS ACADEMIC YEAR 2020/2021 - Novi Yarmaneti (LPPM Ekasakti University, 2022)
Problem important which often faced teacher in activity learning is choose or determine appropriate learning materials or teaching materials in order to help students achieve competence. Thing This is due to the fact that in the curriculum or syllabus, teaching materials are only written down broadly in the form of